Funkcjonowanie i finansowanie europejskiej polityki rynku pracy w czasach światowego kryzysu gospodarczego - Grynia, Alina (Kwartalnik Kolegium Ekonomiczno-Społecznego. Studia i Prace, 2012)
Labour market policy is considered an element of state intervention in market mechanisms as consequence of negative labour market phenomena. Downturn on labour market caused by global economic crisis has led to increase in the number of tasks of LMP aimed at protection of existing jobs, providing social benefits to the unemployed and facilitating job search. Basic instruments of active and passive LMP are presented in the text as well as conditions and effectiveness of their application, and financing in the EU member states during economic crisis. The analysis performed showed that the LMP introduced in different states differed greatly depending on the chosen LMP model. It can be stated that expenses for active and passive instrument increased in all member states during crisis. However, the level of changes differed among the states. The largest increase has been noted among old member states. The largest share of the expenses for LMP was spent on passive LMP. During economic downturn the number of beneficiaries of passive LMP increased. The effectiveness of the instruments used is evaluated differently among the member states. Reliable analysis of LMP effectiveness during crisis requires more time and preparation of unified research methodology.